CD30 expression in a case of intravascular large B‐cell lymphoma, cutaneous variant. (3rd April 2019) - Provasi, Matteo; Bagnoli, Filippo; Fanoni, Daniele; Alberti‐Violetti, Silvia; Tomasini, Dario; Berti, Emilio
Abstract : Intravascular large B‐cell lymphoma (IVLBCL) is one of the rarest B‐cell non‐Hodgkin lymphomas (NHL), with an aggressive clinical behavior and a poor prognosis; in fact, its treatment is still an unmet clinical need, with a 3‐year overall survival (OS) rate of 60% to 81%, and a central nervous system relapse rate of 25%. It usually presents as a widespread disease at diagnosis, with multi‐organ involvement. Previously considered as a diffuse large B‐cell lymphoma variant, it now represents a different extranodal large B‐cell lymphoma entity in the last WHO Classification of tumors of hematopoietic and lymphoid tissues. We hereby describe the case of an 84‐year‐old Italian woman with an IVLBCL, cutaneous variant, who suffered from early relapse after R‐COMP chemotherapy regimen, and was therefore treated with a palliative metronomic chemotherapy. Interestingly, neoplastic cells showed CD30 expression at relapse. CD30 positivity has never been reported in this disease so far, and its expression is known to be involved in NF‐kB activation. CD30 expression may be further studied as for prognostic and therapeutic significance; in fact, new therapeutic strategies, such as antibody‐drug conjugate targeting CD30, are now available.